C-511T polymorphism of interleukin-1 β gene is not associated in type 2 diabetes mellitus - a study in Malaysian population. - Vasudevan, Ramachandran; Ismail, Patimah; Stanslas, Johnson; Shamsudin, Norashikin (Asian Network for Scientific Information, 2008)
The objective of this study is to determine the association between the C-511T polymorphism of Interleukin -1 β gene in T2DM with or without hypertension in Malaysian population. A total of 175 subjects were recruited for this study. Genotyping of C-511T variant was performed by Hot-start PCR-RFLP analysis. The frequency for CC, TC and TT genotypes of C-511T variant in IL-1 β gene was 25.45, 40 and 34.55% in T2DM 25, 51.67 and 23.33% in T2DM with hypertension and 21.66, 36.67 and 41.67% respectively found in controls (p>0.05). This study suggests that there was no significant difference in the genotypic distribution of C-511T polymorphism of IL-1 β gene between T2DM and controls. Therefore, C-511T variant in IL-1 β gene polymorphism is not considered an independent risk factor or not a predictor for T2DM in Malaysian population.